2010
DOI: 10.1016/j.humimm.2009.08.012
|View full text |Cite
|
Sign up to set email alerts
|

HLA class I molecules reflect an altered host proteome after influenza virus infection

Abstract: Class I HLA sample and display peptides from thousands of endogenous proteins at the cell surface. During infection, the influenza virus modifies the host cell proteome by (i) triggering host anti-viral responses, (ii) hijacking host processes, and (iii) inhibiting host mRNA processing. In turn, the catalog of HLA class I peptides that decorate the surface of an infected cell is positioned to reflect an altered host cell proteome. To understand the host-encoded peptides presented by class I molecules following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 46 publications
6
34
1
Order By: Relevance
“…In contrast to previous MS efforts to identify IAV peptides in association with A2 (21,22), the highly conserved M1 58-66 peptide GILGFVFTL was not only detected, but shown to be abundantly presented by infected lung epithelium. Previously unrecognized IAV epitopes were identified and characterized by their copy number on infected cells.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…In contrast to previous MS efforts to identify IAV peptides in association with A2 (21,22), the highly conserved M1 58-66 peptide GILGFVFTL was not only detected, but shown to be abundantly presented by infected lung epithelium. Previously unrecognized IAV epitopes were identified and characterized by their copy number on infected cells.…”
Section: Discussioncontrasting
confidence: 97%
“…S23). Whereas the other six peptides are not fully conserved, variability is still finite, with three variants each covering the HA 431-439 stem region segment and PB2 463-471 and eight peptide variants covering NA [18][19][20][21][22][23][24][25][26] and NS1 [122][123][124][125][126][127][128][129][130] . M1 134-142 global strain variability is accounted for by three peptides but the RMGAVTTES variant found in 13% is predicted to be a very weak A2 binder, potentially permitting viral escape.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viruses, including HIV (10), measles virus (11), influenza virus (12), and respiratory syncytial virus (13), often alter the self-peptide repertoire on MHC class I molecules. Changes in cellular metabolic activity can also skew the repertoire of self-peptides displayed at the cell surface (14).…”
Section: A Ctivated Cytotoxic Cd8mentioning
confidence: 99%
“…9,49 ANXA2 can be incorporated into the IAV particles and supports virus replication by converting plasminogen into plasmin, which can serve as an alternative protease for the cleavage of the hemagglutinin (HA) outside of the respiratory tract. 50−52 In this study, ANXA2 was found to be down-regulated during HPAI H5N1 virus infection (Supplementary Figure 2, Supporting Information).…”
mentioning
confidence: 99%